2015
DOI: 10.1042/bsr20140170
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium toxicity induces ER stress and apoptosis via impairing energy homoeostasis in cardiomyocytes

Abstract: Cadmium, a highly toxic environmental pollutant, is reported to induce toxicity and apoptosis in multiple organs and cells. The present findings showed that cadmium toxicity induces cell stress and promotes apoptosis in cardiomyocytes in a metabolic manner, by either disrupting the glucose metabolism or inhibiting mitochondrial respiratory gene expressions through AKT/mTOR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 28 publications
(31 reference statements)
1
29
0
1
Order By: Relevance
“…In many of the 10 μM Cd-treated larvae that were arched, the pericardium and ventricle were also enlarged, but we did not see evidence of abnormal looping as was reported in the medaka study. Some studies have shown toxic effects of Cd on cultured cardiomyocytes and in whole animals (Chen et al 2015; Ferramola et al 2012). The increased cell death might lower pumping efficiency, and the resulting drop in peripheral blood pressure could induce a compensatory baroreflex in heart rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of the 10 μM Cd-treated larvae that were arched, the pericardium and ventricle were also enlarged, but we did not see evidence of abnormal looping as was reported in the medaka study. Some studies have shown toxic effects of Cd on cultured cardiomyocytes and in whole animals (Chen et al 2015; Ferramola et al 2012). The increased cell death might lower pumping efficiency, and the resulting drop in peripheral blood pressure could induce a compensatory baroreflex in heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Cd affects redox balance and survival in cultured neurons (Lopez et al 2006) and has been linked to amyloid accumulation and progression of neurodegenerative disorders (Jomova et al 2010; Li et al 2012). Cd has also been linked to the progression of heart disease and to toxicity of cardiomyocytes in vivo and in vitro (Chen et al 2015; Ferramola et al 2012; Limaye & Shaikh 1999), further evidence of the broad impact of this metal.…”
Section: Introductionmentioning
confidence: 97%
“…Maternal exposure to cadmium during pregnancy perturbs cardiovascular development of rat offspring which in turn contributes to a long term increased risk of cardiovascular diseases [18]. Cadmium damages vascular tissues, induces endothelial dysfunction and promotes atherosclerosis by oxidative mechanisms [19,20]. In addition to its teratogenic effects, cadmium also causes reproductive toxicity by affecting both testis and oocyte development; increased cadmium concentrations in the ovary have been associated with failure of oocyte development and failure to ovulate [10].…”
Section: Introductionmentioning
confidence: 99%
“…It frequently alters the activity of biological molecules by binding to nitrogen, oxygen, or sulfur-containing groups, eventually disrupting normal cell function [9, 10]. Multiple lines of evidence indicate that apoptosis plays an important role in acute and chronic Cd 2+ intoxication.…”
Section: Introductionmentioning
confidence: 99%